A Systematic Mapping on Executable Models for the Architectural Design of Systems-of-Systems - Lebtag, Bruno G. A.; Teixeira, Paulo Gabriel; Graciano Neto, Valdemar Vicente (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2022: Anais do IV Workshop em Modelagem e Simulação de Sistemas Intensivos em SoftwareDO - 10.5753/mssis.2022.225662, 2022)
Systems-of-Systems (SoS) are complex systems composed of managerially and operationally independent constituent systems (CS). Smart cities are examples of SoS. These types of systems impose challenges to the traditional software architecture design, such as describing heterogeneous CS that are constantly evolving and identifying emergent behaviors from the interactions of those CS. Executable models (ExM) have been envisioned as a possible solution to deal with the challenges raised by SoS architectural design. However, to the best of our knowledge, no systematic mapping study (SMS) exists that investigate current state of art in the research area of SoS architectual design using ExM. Therefore, the main goal of this study is to synthesize evidence of that research area, observing research trends and identifying possible research gaps yet to be explored. Results reveal that (i) the use of model transformation from a static SoS domain-specific language to a ExM is intensely explored and (ii) ExM were used mainly to evaluate and synthesize SoS architectures but also to observe emergent behaviors and to measure quality attributes.